Histopathological Spectrum of Ophthalmic Lesions: A 5 Year Study - Hanmante, Rajharsh D; Suvernakar, S V; Deshpande, S A (Annals of Pathology and Laboratory Medicine, 2018)
Background: Ophthalmic pathology is unique in many respects as it encompasses wide range of tissues - epithelia, connective tissue and specialized tissue. Pathologies ranging from trauma, degenerative, inflammatory and neoplastic conditions can affect any of the various components of orbito-ocular system. This study is designed to review the histopathologic patterns of orbito-ocular specimens sent to the histopathologist. Methods: It is a retrospective review of slides and paraffin-embedded blocks of all ophthalmic specimens received over a period 05 year at the histopathology department. Clinical data including age, sex, site of the lesion and clinical summary were extracted from the histopathology requisition forms. Result: Total 116 cases were studied over a period of 05 year from January 2012 to December 2016. M:F ratio was 1.1:1. Majority of cases (40%) presented during 4 th to 5 th decade of life. Lid was the commonest site of lesion affecting to 61 (52.6%) cases followed by conjunctiva in 27 (23.3%), lacrimal gland in 15 (12.9%) and eye ball in 09 (7.7%) cases. Benign lesions were most common constituting the 43% cases followed by inflammatory lesions (31%) and Malignant (26%). Among the Benign lesions, Naevi was the predominant lesion accounting for 15.5% cases followed by cystic lesions (13%). Among the malignant lesions, Squamous cell carcinoma was the predominant lesions seen in 15 cases, followed by Basal cell carcinoma 04 cases. Sebaceous gland carcinoma (04), Retinoblastoma (03), Hidradenocarcinoma (01), Mucinous carcinoma of eye lid (01), Malignant Melanoma (01) and Verrucous carcinoma (01) were the other malignant lesions. Conclusion: Eye is the vital organ for vision. In our study, Naevi was the most common benign and Squamous cell carcinoma was the most common malignant lesion. Literature data showed that, different geographic areas had predilection for different ophthalmic lesions. Thus, it is emphasized that more studies are needed to know the geographical pattern of ophthalmic lesions.